(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2009)
The advantage and possibility of the cloud point extraction for the preconcentrating of the pharmaceutical preparation and bio-active material were сonsidered. Possibilities of application of the phenol - induced cloud point extraction for the preconcentrating of the labile substances are investigated.